Certificateless multi-signcryption scheme in standard model. (2018) - Wu, Xuguang; Zhang, Minqing; Zhu, Shuaishuai
A signcryption scheme can realise the security objectives of encryption and signature simultaneously, which has lower computational cost and communication overhead than the sign-then-encrypt approach. To adapt multi-user settings and solve key escrow problem of ID-based multi-signcryption schemes, we defined the formal model of certificateless multi-signcryption scheme and proposed a certificateless multi-signcryption scheme in the standard model. The scheme is proved secure against adaptive chosen ciphertext attacks and adaptive chosen message attacks under decisional bilinear Diffie-Hellman assumption and computational Diffie-Hellman assumption respectively.